2013
DOI: 10.1111/gcb.12358
|View full text |Cite
|
Sign up to set email alerts
|

Testing simulations of intra‐ and inter‐annual variation in the plant production response to elevated CO2 against measurements from an 11‐year FACE experiment on grazed pasture

Abstract: Ecosystem models play a crucial role in understanding and evaluating the combined impacts of rising atmospheric CO2 concentration and changing climate on terrestrial ecosystems. However, we are not aware of any studies where the capacity of models to simulate intra- and inter-annual variation in responses to elevated CO2 has been tested against long-term experimental data. Here we tested how well the ecosystem model APSIM/AgPasture was able to simulate the results from a free air carbon dioxide enrichment (FAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…While increased N sequestration in long‐lived plant biomass and soil organic matter and slower decomposition of litter with lower N concentration may contribute to PNL in eCO 2 (Rastetter et al ., ; Luo et al ., ), there are thus also other processes by which eCO 2 may sustain increased plant N acquisition over long time periods (#P1‐3 in Table ). There are examples of long‐term free‐air CO 2 enrichment (FACE) experiments with declining (Norby et al ., ), approximately constant (Schneider et al ., ; McCarthy et al ., ; Reich & Hobbie, ; Li et al ., ; Talhelm et al ., ) or increasing (Schneider et al ., ; Reich & Hobbie, ) temporal response trends of eCO 2 ‐induced productivity enhancement. For forests, it has earlier been indicated that the initial productivity enhancement in eCO 2 declines rapidly during the first few years, but data available at that time only allowed for analysis of temporal response trends of up to five years (Körner, ).…”
Section: Introductionmentioning
confidence: 99%
“…While increased N sequestration in long‐lived plant biomass and soil organic matter and slower decomposition of litter with lower N concentration may contribute to PNL in eCO 2 (Rastetter et al ., ; Luo et al ., ), there are thus also other processes by which eCO 2 may sustain increased plant N acquisition over long time periods (#P1‐3 in Table ). There are examples of long‐term free‐air CO 2 enrichment (FACE) experiments with declining (Norby et al ., ), approximately constant (Schneider et al ., ; McCarthy et al ., ; Reich & Hobbie, ; Li et al ., ; Talhelm et al ., ) or increasing (Schneider et al ., ; Reich & Hobbie, ) temporal response trends of eCO 2 ‐induced productivity enhancement. For forests, it has earlier been indicated that the initial productivity enhancement in eCO 2 declines rapidly during the first few years, but data available at that time only allowed for analysis of temporal response trends of up to five years (Körner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Decreases are less likely where N inputs are maintained either through fertiliser application or by biological nitrogen fixation (Hu et al 2006), as was the case at the Winchmore site. We have previously shown that simulations of grassland responses to CO 2 are very sensitive to the legume content (Li et al 2014), hence the decision to use the measured legume content in the modelling for this study. Further study of other sites varying in soil N availability would be necessary before any general conclusions can be drawn about historical CO 2 × soil interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the inability of the model to capture the full range of interannual variability in NHA; while it does not concern us if we are simply looking at mean responses, this does become important if the object of the study is to examine changes in variability over time. Variability in NHA is a significant issue for farm management (Smit et al 1996, White et al 2010 and is expected to be a dominant influence under climate change (Li et al 2014). The second issue is the difficulty the model shows in simulating actual changes in legume content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Li et al . () suggested improving the representation of plant N demand responses (i.e. higher NUE), pasture legume content and possibly N fixation by legumes in AgPasture.…”
Section: Prospect: Search For Appropriate Responsesmentioning
confidence: 97%